Myocardial revascularization in diabetic patients presenting with critical limbischemia - Ivan Ivanovich Dedov; Victor Yur'evich Kalashnikov; Konstantin Vladimirovich Melkozerov (Сахарный диабет)
The frequency of diabetic complications remains high despite the development of improved therapeutic modalities. Macroangiopathy continues to bethe predominant complication while coronary heart disease is the main cause of mortality.This paper considers clinical features of diabetic patientswith coronary heart disease and critical limb ischemia; various aspects of optimal drug therapy, preoperative examination and diagnostics precedingvascular non-cardiac surgery; preoperative risk assessment; indications for coronary angiography and myocardial revascularization. The authors emphasizethe importance of development of algorithms for the treatment of patients with diabetes, critical limb ischemia, and coronary heart disease.